Uṡirul Tasyī’u fi Taṣīḥul Hadīṡi: Durāsatu ‘An Taṣīḥi Abī ‘Abdillāḥil Hākimil Nisābawī Hadīṡiyyul Ṫīru wa min Kuntu Maulāhu fi’liyyu Maulāhu fī Kitābil Mustadriku ‘Ala Ṣaḥīḥīna - Abdul Malik Gazali (Center for Research and Development of Religious Literature and Heritage, 2013)
-